Pengaruh Tambahan Serat Sabut Kelapa terhadap Kuat Tekan dan Kuat Tarik Belah Beton - Prayogi, Galih (Jurnal Proyek Teknik Sipil, 2024)
Concrete has a weakness against tensile forces. One way to improveconcrete's weakness in tensile strength is by adding fiber to the concrete mix which iscalled fiber concrete. This research was to determine the compressive strength andsplit tensile strength of normal concrete with the addition of coconut fiber aged 7days, 14 days, and 28 days. The percentage of additional coconut fiber fiber is 0.5%;2.5%; 4.5%; 6.5%; and 8.5% of the total volume of concrete. Testing the compressivestrength and split tensile strength of concrete used cylindrical samples with adiameter of 10 cm and a height of 20 cm. The fiber used is coconut fiber with a lengthof 30 mm. The compressive strength value of concrete without the addition of fiber at28 days was 31.33 MPa, while concrete with the addition of 0.5%; 2.5%; 4.5%; 6.5%;and 8.5% coconut fiber obtained compressive strength values of 33.05 MParespectively; 33.72 MPa; 24.46 MPa; 16.47 MPa; and 9.23 MPa. The split tensilestrength value of concrete without the addition of fiber at 28 days was 2.835 MPa,while concrete with the addition of 0.5%; 2.5%; 4.5%; 6.5%; and 8.5% coconut fiberobtained split tensile strength values of 3.497 MPa respectively; 3,754 MPa; 4,029MPa; 3,345 MPa; and 3.039 MPa, while the maximum compressive strength valueoccurs in the 2.5% variation concrete with the addition of coconut fiber, namely33.05 MPa, while the maximum split tensile strength value occurs in the 4.5%variation concrete with the addition of coconut fiber fiber, namely 4,029 MPa. Theresults ofthe split tensile strength equation based on the compressive strength valueof concrete at a percentage of 0% were 0.507√f'c, while in concrete the addition ofcoconut fiber was at 0.5%; 2.5%; 4.5%; 6.5%; and 8.5% respectively amounted to0.608√f'c; 0.646√f'c; 0.815√f'c 0.824√f'c 1.0004√f'c.